"Figuring stuff out myself" - a qualitative study on maternal vaccination in socially and ethnically diverse areas in England - Sima Berendes; Sandra Mounier-Jack; Oyinkansola Ojo-Aromokudu; Alice Ivory; Joseph D. Tucker; Heidi J. Larson; Caroline Free (BMC, 2023)
Abstract Background Maternal vaccinations against Influenza, Pertussis, and Covid-19 are recommended in the UK, and vaccines against further infections may become available soon. However, many pregnant women, especially in socially and ethnically diverse areas, have low vaccine uptake. Qualitative studies on the reasons and possible solutions are needed that are inclusive of disadvantaged and minority ethnic groups. We therefore aimed to understand the complex interplay between structural and behavioural factors contributing to the low maternal vaccine uptake in socially and ethnically diverse areas in London in the Covid-19 context. Methods In 2022, we conducted semi-structured interviews and a focus group discussion among a purposive sample of 38 pregnant/recently pregnant women and 20 health service providers, including 12 midwives. Participants were recruited in ethnically diverse London boroughs. We followed a critical realist paradigm and used a thematic analysis approach. Results The sample included participants who took all, some or none of the maternal vaccines, with some participants unsure whether they had taken or been offered the vaccines. Decision-making was passive or active, with the expectation for pregnant women to do their 'own research'. Participants described various individual, social and contextual influences on their decision-making as they navigated the antenatal care system. Missing or conflicting information from providers meant knowledge gaps were sometimes filled with misinformation from unreliable sources that increased uncertainties and mistrust. Both pregnant women and providers described structural and organisational factors that hindered access to information and vaccinations, including lack of training, time and resources, and shortcomings of health information systems and apps. Some participants described factors that facilitated vaccination uptake and many made recommendations for improvements. Conclusions Our study showed how structural and organisational factors can compound uncertainties around maternal vaccination among socially and ethnically diverse populations. Results highlight the need for more reliable resources, streamlined workflows, improved electronic information systems and training in their use. Roles and responsibilities should be clarified with potential greater involvement of nurses and pharmacists in vaccine provision. Education and communication should consider individual (language/digital) skills and needs for information and reassurance. Further research is needed to co-produce solutions with service users and providers.